PENGARUH FASILITAS KERJA, KEPUASAN KERJA, DAN REWARD EKSTRINSIK TERHADAP KINERJA PEGAWAI (Studi Kasus Pada P.O. Haryanto Kudus) - Akbar Saiku Maulana; Dita Prameswari (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2026)
Background & Purpose: This study emphasizes that employee performance is a crucialelement for organizational success, particularly in the transportation sector, which presentsunique work challenges. At P.O. Haryanto Kudus, employee performance is influenced bywork facilities, job satisfaction, and extrinsic rewards. Given the limited simultaneous studyof these three factors in the transportation industry, this study was conducted to analyzetheir influence and provide practical recommendations for improving human resourcequality.Method: This study uses a quantitative method with a positivistic approach to analyze theinfluence of work facilities, job satisfaction, and extrinsic rewards on employeeperformance at P.O. Haryanto Kudus. Primary data were collected through a Likert-basedquestionnaire distributed to 67 respondents, who were determined using a simple randomsampling technique from a population of 200 employees. Data analysis was carried outusing Partial Least Square (PLS).Results: The results of the study indicate that providing work facilities plays a significantrole in improving employee performance at P.O. Haryanto Kudus Branch. Adequatefacilities, particularly work tools and equipment, have been shown to boost employeeproductivity, work ethic, and effectiveness in carrying out their duties. This finding alignswith previous research that emphasized the importance of facilities as a strategic factor insupporting employee morale and performance. Therefore, company management needs toconsistently identify and fulfill work facility needs as an effort to optimize employeeperformance and achieve organizational goals.Conclusion & Suggestion: This study concludes that work facilities and job satisfactionhave a significant positive effect on employee performance at P.O. Haryanto Kudus, whileextrinsic rewards have no significant effect. This demonstrates the importance of providingadequate facilities and increasing job satisfaction as key strategies in boosting productivity,while the reward system needs to be evaluated to be more performance-based.Theoretically, these findings support the Work Environment Theory, the Two-FactorTheory, and the Reinforcement Theory, but further research is needed in other sectors withbroader variables